A evolução da teoria quantitativa da moeda: uma perspectiva de compreensão histórico-teórica - CARVALHO, David Ferreira (Associação Keynesiana Brasileira, 2022)
The Quantitative Theory of Currency (also known as TQM) represents, in essence, the theory used by classical economists to demonstrate that the variation in the general price level is determined by the variation in the quantity of money, when analyzing the economy as a whole. There are different approaches that represent TQM in the field of economic sciences, such as those developed by John Richard Hicks, Irving Fisher, Cambridge School and John Maynard Keynes. This article intends to carry out an extensive analysis around the evolution of TQM from a perspective of historical-theoretical understanding, including presenting – in a critical form – the substance of the version of a new and original TQM equation on entirely different bases from the versions previous ones.